PERANCANGAN SISTEM INFORMASI PRODUKSI DEPARTEMEN ASSEMBLING BERBASIS VISUAL BASIC.NET DAN MICROSOFT ACCESS DI PT JONAN INDONESIA (SAINTEKBU, 2021)
Supply of goods information system  at jonan indonesia  is use running  has using  the computer but  it is use only in the  field of administration  while the marketing  still used the manual wraiting .There fore  it is necessary to computer based information system supply of goods better sofware .The aimed for this supply of goods  informatin system simplify the processing of supplier data in detail , precise and accurate. The metods of data  collection  used is by doing observation and interview  and is  equipped with a literature review  that has a close relevance to the subject matter.       Microsoft visual studio 2010 was chosen to be a software in making the information system of  home supply of goods and using  microsoft acces 2007 database.This supply of goods  information  system  is made to facilitate the administrative  work of consumer data because data received administration is computerized . The suggestion given is to develop and refine this system to complete the existing  facilities.